In vitro seed germination and Growth of Three Varieties of Black Gram after Ultraviolet-B Radiation - Rajendiran, K; Thiruvarasan, K; Vijayalakshmi, R (International Journal of Applied Sciences and Biotechnology, 2016)
In vitro seed germination and growth of seedlings was tried with three varieties of black gram (Vigna mungo (L.) Hepper) viz. Vamban-3, Nirmal-7 and T-9 after ultraviolet-B irradiation (UV-B = 2 hours once with 1 hour recovery time @ 12.2 kJ m-2 d-1; ambient = 10 kJ m-2 d-1). Unstressed and UV-B stressed VAMBAN-3 and T-9 seeds both in dry and wet conditions responded to in vitro germination. Unstressed NIRMAL-7 failed to germinate under in vitro culture. UV-B stressed NIRMAL-7 responded to in vitro culture. UV-B irradiation enhanced seedling height at both dry and wet conditions in VAMBAN-3 followed by NIRMAL-7 compared with controls. Root and shoot length of UV-B stressed VAMBAN-3 and NIRMAL-7 performed five to six times better than control. Root and shoot length of T-9 was reduced (2.61 to 8.69 %) below control after UV-B exposure. UV-B stressed VAMBAN-3 under dry and wet exposure accumulated three to six times more plant biomass over controls. UV-B stressed NIRMAL-7 and T-9 dry seeds accumulated less plant biomass by 70.86 % and 12.39 % respectively than their controls. NIRMAL-7 and T-9 under dry UV-B exposure produced two times more leaves than control. Int J Appl Sci Biotechnol, Vol 4(1): 117-129